Ultrastructural analysis of the contractile apparatus in the rat’s heart on the stages of ontogeny - Kozlov S.V.; Mayevsky A.E.; Mіshalov V.D.; Sulayeva O.N. (Морфологія, 2015)
Background. Cardiovascular disease is a major cause of human mortality and disability at working age. Many disorders of cardiac sarcomeres components have been linked to human cardiomyopathies, including desminopathy, dilated cardiomyopathy, hypertrophic cardiomyopathy, familial atrial septal defects, and others. Objective. The aim of this work was to determine the remodeling of the contractile apparatus in cardiomyocytes in rat ventricular myocardium on the stages of ontogeny. Methods. White rats were used as a material. Hearts were investigated by the transmission electron microscopy during the stages of prenatal and postnatal ontogeny. Results. Active myofibrilogenesis observed at 18th day of development and dominated in the right ventricle of myocardium during fetal development. After birth there was alignment of myofibrils content in the myocardium of both ventricles. Rapid growth of myofibrils content was seen in the sarcoplasm of cardiomyocytes, which took priority of development in the left ventricle during the period from the 3rd to the 14th day of postnatal ontogeny. At 30th day after the birth the contractile apparatus in the rat’s ventricular myocardium acquired signs of maturity. Conclusion. Development of the contractile apparatus in the rat’s ventricular myocardium is nonlinear and depends on the functional load of heart chamber.